Предмет: Алгебра,
автор: дина4455
Помогите решить примеры?
Приложения:
Ответы
Автор ответа:
0
(х+3)2+=х2+9+6х
(х+2)2=х2+4+4х
(х-1)2=х2+1-2х
(х-2)2+24=х2+4-4х+24
(х-3)(х+3)=х×х+х×3-3×3-3×х=х2+3х-9-3х=х2-9
(х+2)2=х2+4+4х
(х-1)2=х2+1-2х
(х-2)2+24=х2+4-4х+24
(х-3)(х+3)=х×х+х×3-3×3-3×х=х2+3х-9-3х=х2-9
Автор ответа:
0
1)
x+1=0 x=-1
x+3=0 x=-3
2)
(x-3)(x+13)=0
x-3=0 x=3
x+13=0 x=-13
4)
(x+3)(x-1)=0
x+3=0 x=-3
x-1=0 x=1
x+1=0 x=-1
x+3=0 x=-3
2)
(x-3)(x+13)=0
x-3=0 x=3
x+13=0 x=-13
4)
(x+3)(x-1)=0
x+3=0 x=-3
x-1=0 x=1
Автор ответа:
0
5) x^2-9-5x+13=0 x^2-5x+4=0 (x-4)(x-1)=0 x-4=0 x=4 и x-1=0 x=1
Автор ответа:
0
в 3 может ошибка?
Похожие вопросы
Предмет: Українська мова,
автор: Аноним
Предмет: Қазақ тiлi,
автор: davidggok06777
Предмет: Русский язык,
автор: asanbekovomurbek777
Предмет: Математика,
автор: alex0079k